Application of WASP model to simulate water pollution control of Duriangkang Dam. Issue 1 (5th January 2021) - Wimordi, Calvin; Yudianto, Doddi; Guan, Yiqing
Abstract: Located in Batam City, Duriangkang Dam plays an essential role in providing clean water in the area, also being the first and largest estuary dam in Indonesia. However, with a total effective water volume of 107, 000, 000 m 3, Duriangkang Dam is now heavily polluted because of enormous wastewater loads from both domestic and industrial sources that are directly discharged into the dam. The practice of fish farming has also contributed to its demise. Based on water samples collected during 2016 to 2018, the water condition for Duriangkang Dam is no longer classified as the 2nd class of raw water, based on Indonesian water standards. The present study utilizes the WASP model to evaluate and simulate possible solutions for controlling the Duriangkang Dam water pollution rate. The water quality indicators of dissolved oxygen (DO), total phosphorus (TP) and biochemical oxygen demand (BOD) concentrations are modelled. The calibration and verification results indicate the model exhibited an excellent fitting for DO, BOD and TP concentrations. Under several scenarios, it was determined that the best way to control the pollution rate within the dam is by implementing scenario 8, which include total control of the fish farms and domestic wastewater loads.